2013
DOI: 10.1038/nmeth.2759
|View full text |Cite
|
Sign up to set email alerts
|

A chemoproteomic platform to quantitatively map targets of lipid-derived electrophiles

Abstract: Cells produce electrophilic products with the potential to modify and affect the function of proteins. Chemoproteomic methods have provided a means to qualitatively inventory proteins targeted by endogenous electrophiles; however, ascertaining the potency and specificity of these reactions to identify the most sensitive sites in the proteome to electrophilic modification requires more quantitative methods. Here, we describe a competitive activity-based profiling method for quantifying the reactivity of electro… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

4
306
0
1

Year Published

2015
2015
2022
2022

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 268 publications
(311 citation statements)
references
References 44 publications
4
306
0
1
Order By: Relevance
“…Energy metabolism enzymes are one of the main classes of proteins that contain highly reactive cysteines. Among them, several studies identified critical cysteine residues from the brain form of GP (22)(23)(24)(25)(26).…”
mentioning
confidence: 99%
“…Energy metabolism enzymes are one of the main classes of proteins that contain highly reactive cysteines. Among them, several studies identified critical cysteine residues from the brain form of GP (22)(23)(24)(25)(26).…”
mentioning
confidence: 99%
“…In addition to being activated by Stx-and ricin-mediated ribotoxic stress, ZAK signaling and/or expression also has been associated with cardiac hypertrophy (45,46); G 2 /M cell cycle arrest in response to gamma irradiation (47); metastasis (48); gastric, colon, and bladder cancers (49,50); doxorubicin toxicity (51); anisomycin treatment; exposure to UV irradiation (26); osmotic shock (52); and oxidative stress (53), suggesting that ZAK transduces a number of different stress responses.…”
Section: Discussionmentioning
confidence: 99%
“…Proteomic studies revealed highly reactive cysteine residues in bGP (Cys 109 , Cys 326 , and Cys 496 ) (25)(26)(27), which can constitute potent targets of electrophilic compounds such as DTCs. Consequently, DTCs may directly modulate glycogenolysis through the modification of key cysteine residues of bGP, known to redox regulate the enzyme activity.…”
Section: Discussionmentioning
confidence: 99%
“…Rat models and recent proteomic studies suggested that brain glycogen phosphorylase is a putative target of DTC chemicals in the brain (7). In addition, this isoenzyme has been described as presenting highly reactive cysteine residues (23,(25)(26)(27). To further determine the impact of DTCs on bGP activity and glycogen metabolism in the brain, we treated mice brain extracts with thiram (Fig.…”
Section: Edited By Ruma Banerjeementioning
confidence: 99%